AI Integration in Academic Pursuits: A Phenomenological Exploration - Godinez, Lenny; Bacang, Angela Gabrielle (Journal of Interdisciplinary Perspectives, 2025)
This study addressed a gap in research regarding graduate students' perceptions and use of Artificial Intelligence (AI) tools in higher education, specifically focusing on English majors. Using Colaizzi's phenomenological approach and purposive sampling technique, the researcher conducted semi-structured interviews with seven participants from a private university in Dumaguete City. The findings revealed that integrating AI into academic tasks significantly enhanced students' educational experiences by improving research efficiency, writing quality, creativity, and access to diverse resources. However, concerns about AI reliability and over-reliance were also highlighted. Six themes emerged that illustrated students' AI utilization: (1) Discernment, which involved assessing AI-generated content; (2) Caution, emphasizing the need for ethical use and vigilance against misinformation; (3) Balance, reflecting efforts to integrate AI support while maintaining scholarly voice; (4) Efficiency, highlighting the increased speed of completing research and writing tasks; (5) Confusion, arising from varied experiences with AI; and (6) Independence, encapsulating the desire to maintain critical thinking despite AI assistance. This study enhanced understanding of the complexities of technology integration in education and offered practical recommendations for educators on ethical AI use. Key contributions included advocating for developing programs and workshops focused on responsible AI use and encouraging independent thought and critical engagement among students. Ultimately, this research aimed to inform teaching practices in a digital learning environment and equip students to navigate the challenges and opportunities presented by technological advancements. It offered valuable insights into how graduate students managed the integration of AI in their academic pursuits, thus contributing to the ongoing discourse on technology in education.